EVALUASI TINGKAT KEMATANGAN IMPLEMENTASI SCRUM BERBASIS SCRUM BODY OF KNOWLEDGE - Yusuf, Andi Akram (AI Society & STMIK Indonesia, 2025)
The banking industry’s core business involves collecting public funds and distribute them into loans. Intense competition within the banking sector demands speed in business development processes, including the development of mobile banking applications. At PT Bank XYZ, the Mobile Banking Team develops mobile banking applications by implementing the Agile methodology and adopting the Scrum framework. The choice of the Scrum framework aims to facilitate the development of small-value features that can be quickly released, thus creating significant value for users. The faster this value reaches the end users, the quicker user feedback can be gathered for further improvements. However, the implementation of Scrum has not been fully effective, as evidenced by the presence of carried-over features and feature enhancements. This research employs a mixed-method approach with an exploratory sequential design, starting with qualitative research followed by quantitative research. Qualitative data were collected through observations and interviews, while quantitative data were gathered through questionnaires. The questionnaires were developed using the Scrum Body of Knowledge (SBOK). The data were then processed using the KPA Rating method. The results indicate that the implementation is still at Level 1 (Explored). Recommendations are formulated based on SBOK and focus on achieving Level 2 (Defined) and Level 3 (Improved). Level 4 was not included in the recommendations, as mobile banking development at PT Bank XYZ has not yet reached the enterprise stage.